New Hope for Genome Editing in Cultivated Grasses: CRISPR Variants and Application - Riaz, Asad; Kanwal, Farah; Ahmad, Iqrar; Ahmad, Shakeel; Farooq, Ayesha; Madsen, Claus Krogh; Brinch-Pedersen, Henrik; Bekalu, Zelalem Eshetu; Dai, Fei; Zhang, Guoping; Alqudah, Ahmad M. (Frontiers in Genetics, 2022)
With the advent of Clustered Regularly Interspaced Palindromic Repeats (CRISPR) and CRISPR-associated protein (Cas) mediated genome editing, crop improvement has progressed significantly in recent years. In this genome editing tool, CRISPR-associated Cas nucleases are restricted to their target of DNA by their preferred protospacer adjacent motifs (PAMs). A number of CRISPR-Cas variants have been developed e.g. CRISPR-Cas9, -Cas12a and -Cas12b, with different PAM requirements. In this mini-review, we briefly explain the components of the CRISPR-based genome editing tool for crop improvement. Moreover, we intend to highlight the information of the latest development and breakthrough in CRISPR technology, with a focus on a comparison of major variants (CRISPR-Cas9, -Cas12a and -Cas12b) to the newly developed CRISPR-SpRY that have nearly PAM-less genome editing ability. Additionally, we briefly explain the application of CRISPR technology in the improvement of cultivated grasses with regard to biotic and abiotic stress tolerance as well as improving the quality and yield.